Not languishing but flourishing: The message of positive psychology on ageing - Ágota, Kun (Magyar Gerontológia, 2023)
Traditional psychology approaches the psychological functioning of ageing primarily in terms of problems and difficulties, focusing on the deterioration of abilities, the onset of mental disorders, inactivity and the decline of relationships. However, with the emergence of positive psychology, a different way of thinking emerged, along which the concept of positive ageing was born.